Influence of light quality on the profiling of metabolites and the status of Lactobacillus community in the phyllosphere of hydroponically grown ginseng - Nooruddin Bin Sadiq; Ji-Eun Lee; Muhammad Hamayun; Seda Nur Kabadayı; Na-Yun Park; Bokyung Lee; Ho-Youn Kim (Chemical and Biological Technologies in Agriculture)
Abstract Background The microbial community within the phyllosphere plays a critical role in plant health and growth by facilitating nutrient uptake, inducing resistance and enhancing tolrance to stress. Environmental factors, such as light intensity and quality, are known to influence the composition and function of phyllosphere microbiota. In hydroponic systems, these interactions are particularly relevant, as they can significantly affect plant growth and yield. Based on the potential of controlled environments to shape both plant and microbial responses, the impact of different light conditions on the phyllosphere microbiota is crucial for plant health and productivity. Methods This study evaluated two Korean ginseng varieties exposed to different LED light treatments in a hydroponic system. Metabolite profiling and ginsenoside content were analysed, while bacterial abundance in the phyllosphere was quantified. Detailed insights into the microbial community were obtained through 16S rRNA sequencing. A multivariate analysis was performed to distinguish the effects of different LED treatments of the phyllosphere microbiota. Results Carbohydrates were most abundant in treatments with flouresence light (FL), blue light (BL), and red light (RD), while treatments with dark (DK), infrared (IR), and ultraviolet (UV) light exhibited higher levels of amino acids and organic acids. Minor ginsenoside content was significantly higher in Gumpoong (V2) variety compared to the Yunpoong (V1). Light intensity had a direct impact on the composition of the phyllosphere microbiota, with specific microorganisms being associated with each ginseng variety under different LED light exposures. Organic acids and amino acids positively influenced the abundance of Proteobacteria, Actinobacteria, Chloroflexi, and Ni-trospirae, while Firmicutes, Acidobacteria, Planctomycetes, and Cyanobacteria correlated significantly with carbohydrate levels. Proteobacteria remained stable under IR treatment, constituting over 80% in V2 and 60% in V1, while UV light promoted microbial stability in V2 and fostered more diverse ecosystems in V1, both characterized by richness in organic acids and amino acids. Lactiplantibacillus plantarum was the only lactic acid bacterium detected in both varieties, with higher abundance in V2, indicating its potential ubiquity across different ginseng types. Conclusions Current findings showed that LED light treatments significantly influenced the metabolite profiles and phyllosphere microbiota of hydroponically grown Korean ginseng. Specific light conditions, such as blue, red, and infrared, promoted distinct microbial communities and enhanced the production of key metabolites, including carbohydrates, amino acids, and ginsenosides. The presence L. plantarum, highlights the potential of ginseng as a functional food with probiotic properties. This study provides valuable insights into optimizing ginseng cultivation for both enhanced metabolite production and microbiome health. Graphical Abstract